Effect of a motor behavior course on kinesiology students' attitudes toward disability: A quasi-experimental study - Logan, Samuel W; Case, Layne; Bogart, Kathleen R; Woekel, Erica (European Journal of Adapted Physical Activity, 2023)
This quasi-experimental study used a nonrandomized, control group pre-test post-test research design to determine the effect of a motor behavior course with a social justice perspective on undergraduate students' attitudes toward people with disabilities, alignment with the medical and social models of disability, and mobility beliefs. Undergraduate students enrolled at a public university (n=714) completed survey measures before and after participation in a 10-week course. Intervention group participants (n=357) were drawn from a required course for Kinesiology students that included social justice topics and video-based contact with people with disabilities. Control group participants (n=357) were drawn from a required course for all students that did not include social justice content. Separate one-way ANCOVAs were conducted to identify differences in outcomes between groups, controlling for baseline measures and demographic characteristics. Results indicate that participants in the intervention group reported more favorable attitudes toward people with disabilities, lower medical model scores, higher social model scores, and more favorable views toward self-directed mobility as a human right. Integrating social justice concepts into the classroom may be an important addition to undergraduate Kinesiology curriculums and a valuable intervention strategy to positively influence Kinesiology student attitudes.
Keywords: sociální spravedlnost; studenti lékařství; pohybová aktivita; postižení; postoj ke zdraví; Attitude to Health; Motor Activity; studium lékařství; Humans; Persons with Disabilities; kineziologie aplikovaná; Education, Medical; lidé; Sentiment Analysis; Social Justice; Kinesiology, Applied; postojová analýza; Students, Medical